Post incorporation monitoring into the Brazilian Public Health System: an analysis of Infliximab, Vedolizumab and Tofacitinib for the treatment of ulcerative retocolitis - Barreto Ribeiro dos Santos, Jéssica; Oliveira Lyrio, Amanda; Ferré, Felipe; Pires Mega, Tacila; de Freitas Lopes, Ana Carolina; Fontes Schluckebier Bonan, Luciene (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2025)
Objective: to evaluate the implementation, use, cost of treatment per patient-year and the budgetary impact of infliximab, vedolizumab and tofacitinib for the treatment of mo- derate to severe ulcerative colitis in the SUS. Methods: A retrospective cohort study was carried out using the Open Health Intelligence Situation Room, which originates from the SUS Ambulatory Information System. All patients with primary ICD-10 ulcerative colitis and using infliximab, vedolizumab or tofacitinib were included. The analysis period was from May 2020 to December 2022. Results: After incorporation into the SUS, the time for medicines to become available ranged from 7 to 20 months. Infliximab was the most used (55%), but vedolizumab spread faster, with approximately 60 new patients per month, followed by infliximab and tofacitinib with approximately 35 and 18 patients, respectively. Unit prices for medicines were lower than those proposed in the incorpora- tion, except for tofacitinib in the last acquisition. In 2021, the cost per patient-year was similar for infliximab and vedolizumab. In 2022, vedolizumab had the highest cost. The budgetary impact of infliximab and vedolizumab was similar in the first year of imple- mentation and both had a lower budgetary impact than estimated at incorporation. In the second year of infliximab implementation, the budgetary impact almost doubled due to the greater dissemination of the drug. Conclusion: This analysis presents real-world data, verifying the importance of monitoring the technologies incorporated by the SUS.